Measurements of the latitudinal distributions of total electron content during equatorial spread F events - Valladares, C. E. (2001)
We have constructed latitudinal profiles of the total electron content (TEC) using measurements from six GPS receivers conducted during 1998. The TEC profiles have been divided into two groups: One corresponds to days when plumes or equatorial spread F (ESF) develops, and the second group portrays days of no-ESF condition. The presence/absence of ESF is based on the signature of the coherent echoes measured by the Jicamarca Unattended Long-Term Investigation (JULIA) radar and records of scintillations from two sites spaced in latitude. One scintillation station is located near the magnetic equator (Ancon) and the other 12° southward (Antofagasta). The TEC profiles display the typical day-to-day and seasonal variability seen at low latitudes. During the equinoxes, we observed quite often the crests of the anomaly located between 12° and 20° away from the magnetic equator and a trough in-between. The monthly distribution of the appearance of the anomaly and the local time of their appearance are in very good agreement with the reported variability of the upward vertical drifts and the current theory of the equatorial fountain effect. During the equinoxes and the December solstice, the TEC anomaly is observed almost every day, sometimes when there is no ESF activity. Nevertheless, fine inspection of the TEC latitudinal profiles suggests the existence of a close relationship between the temporal evolution of the TEC profiles near sunset and the onset of ESF. We have examined the TEC latitudinal distributions in two different ways. First, we calculated time difference profiles using the distributions corresponding to 1800 and 2000 LT. Second, we used a parameterization of the TEC distributions obtained at 2000 LT. The first method indicates quite drastic increases of the crest values and sharp decreases near the trough during ESF days. In contrast, during days of no ESF there exist almost uniform TEC decreases at all latitudes. The second method displays a preferred high crest/trough ratio (2), small TEC values at the trough, and large latitudinal integrated values during ESF events.